2003
DOI: 10.1242/dev.00404
|View full text |Cite
|
Sign up to set email alerts
|

The bHLH protein Dimmed controls neuroendocrine cell differentiation inDrosophila

Abstract: Neuroendocrine cells are specialized to produce, maintain and release large stores of secretory peptides. We show that the Drosophila dimmed/Mist1 bHLH gene confers such a pro-secretory phenotype on neuroendocrine cells. dimmed is expressed selectively in central and peripheral neuroendocrine cells. In dimmed mutants, these cells survive, and adopt normal cell fates and morphology. However, they display greatly diminished levels of secretory peptide mRNAs, and of diverse peptides and proteins destined for regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
256
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(277 citation statements)
references
References 43 publications
18
256
2
1
Order By: Relevance
“…As newly made peptides can be released preferentially (21,24), transcriptional regulation that alters DCV content can change the mixture of neuropeptides released at the nerve terminal. Second, DCV capture is itself increased by the transcription factor DIMM, which was known to increase the accumulation of neuropeptidecontaining DCVs in central neurons (10,13). Presumably, DIMM induces a gene encoding for a presynaptic DCV capture effector, which might be regulated by kinases and G proteins (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As newly made peptides can be released preferentially (21,24), transcriptional regulation that alters DCV content can change the mixture of neuropeptides released at the nerve terminal. Second, DCV capture is itself increased by the transcription factor DIMM, which was known to increase the accumulation of neuropeptidecontaining DCVs in central neurons (10,13). Presumably, DIMM induces a gene encoding for a presynaptic DCV capture effector, which might be regulated by kinases and G proteins (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor DIMM regulates the capacity to accumulate amidated neuropeptide-containing DCVs in a subpopulation (∼3%) of Drosophila neurons without regulating neuropeptide gene expression (10)(11)(12)(13)22). Although this could be assumed to reflect an effect on DCV synthesis that is not cargo-specific, the above results from type Ib and III boutons suggested the alternative possibility that DIMM promotes DCV capture.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…pm-Cherry-GFP-Atg8a was a gift from Dr. Tor Erik Rusten (University of Oslo, Oslo, Norway). c929-Gal4 [93] was kindly provided by Dr. Paul Taghert (Washington University, St. Louis).…”
Section: Methodsmentioning
confidence: 99%
“…To define the role(s) of N CCAP in bursicon release and to better understand the molecular and cellular determinants of tanning and wing expansion in Drosophila, we have characterized the adult distribution of bursicon and shown that the hormone localizes to a subset of N CCAP primarily included in the expression pattern of the enhancer-trap line c929-Gal4 (Hewes et al, 2003). We have compared the physiological effects of targeted manipulations of N CCAP , and of the subset of N CCAP within the c929-Gal4 pattern (N CCAP -c929), to show that N CCAP consists of two functionally distinct groups of neurons that interact to regulate release of bursicon into the hemolymph from the abdominal ganglion in a PKA-dependent manner.…”
Section: Introductionmentioning
confidence: 99%